Studi Eksperimen Pengaruh Sudut Serang Terhadap Performa Turbin Angin Sumbu Horisontal NACA 4415 - Susanto, Andi; , Nur Aklis, S.T., M.Eng; , Ir. Subroto, MT (2015)
The aim of this study was to determine effect the angle of attack on the resulting performance of horizontal axis wind turbines with airfoil blade design a variation of type naca 4415 used the angle of attack is the angle of attack 0˚ , 3˚ and 5˚. Angle of attack is the angle formed by the bowstring an airfoil with angle of flow through it, Testing was started by installing wind turbine blades at various angles of attack that has been determined, wind turbine blades totaling 3 blades with a diameter of 3 meters using airfoil type naca 4415. Data capture is then performed using the data measuring instrument looger, anemometer and tachometer. In the test condition without loading the data taken is the wind speed and wind turbine rotor rotation, whereas the testing conditions burdened by the light bulb captured data is the average wind speed , voltage, amperage and energy from the generator. Results of testing wind turbine burdened light bulb indicates that the variation of the angle of attack affect the accumulation of energy produced by wind turbines, this is indicated in the same wind speed is 8,933 m / s accumulation of energy produced at the angle of attack at 2:35 watt.jam 3˚ and the accumulated energy on the variation of the angle of attack at 2:34 5˚ watt.jam, while the influence of variation of the angle of attack of the wind turbine power coefficient ditujukkan the coefficient of variation of the angle of attack 0˚ power generated is equal to 0.01269, the angle of attack power coefficient that is equal to 0.016517 3˚, and the coefficient of variation of the angle of attack power on 5˚ that is equal to 0.010395